2008
DOI: 10.1103/physrevb.78.054422
|View full text |Cite
|
Sign up to set email alerts
|

Muon spin relaxation detection of the soft mode toward the exotic magnetic ground state in the bond-disordered quantum spin systemIPA-Cu(Cl0.35Br0.65

Abstract: The spin-gap system with a bond-disorder ͑CH 3 ͒ 2 CHNH 3 -Cu͑Cl x Br 1−x ͒ 3 is reported by experiments on macroscopic quantities of the uniform susceptibility and the specific heat to show a magnetic order at low temperatures ͑when the value of x is within the limited region between 0.44 and 0.87͒ and otherwise a gapped behavior. We have investigated microscopically the ground state of the sample with x = 0.35 by muon spin relaxation ͑SR͒ to observe that the frequency spectrum of the spin fluctuation tends t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…[38][39][40][41] In this case, the change of continues to increase in low magnetic fields, which indicates a magnetic ground state at the absolute zero. Figure 7 shows the relative temperature change in the muon-spin-relaxation rate of Tl 1−x K x CuCl 3 with x = 0.51 in each longitudinal field, which is evaluated by the same procedure with the case of x = 0.60.…”
Section: Resultsmentioning
confidence: 98%
“…[38][39][40][41] In this case, the change of continues to increase in low magnetic fields, which indicates a magnetic ground state at the absolute zero. Figure 7 shows the relative temperature change in the muon-spin-relaxation rate of Tl 1−x K x CuCl 3 with x = 0.51 in each longitudinal field, which is evaluated by the same procedure with the case of x = 0.60.…”
Section: Resultsmentioning
confidence: 98%
“…, where τ = 1/f is the correlation time of muon spins [14,15,16]. In other words, the distribution is "white".…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of a dynamically fluctuating field, on the other hand, one can obtain its Fourier amplitude with frequency ω=γH LF as a muon spin depolarization rate λ under a static longitudinal field H LF applied along the muon spin direction. Thus, one must note that H LF dependence of λ directly maps the Fourier spectrum of the electron spin fluctuation 21,22) . Now, we start with our result of zero-field μSR.…”
mentioning
confidence: 99%
“…A preliminary μSR experiment had been performed sometime ago by Ohira et al 16) who reported a slight increase in the zero-field (ZF) muon spin depolarization rate λ at low temperatures below 3 K. However, ZF-λ is dependent both on the local field amplitude H local and the characteristic frequency ω c of the spin fluctuation, so that it does not identify what change in the spin state takes place. In this study therefore we worked on longitudinal decoupling (LF) measurements to detect directly the Fourier spectrum of spin fluctuation 21) in single crystals of κ-(BEDT-TTF) 2 Cu(CN) 3 to understand its magnetic state.…”
mentioning
confidence: 99%